Recent experience with use of high definition seismic reflection for nickel sulphide exploration in Western Australia - Williams, P.; Urosevic, Milovan; Kepic, Anton; Whitford, M. (EAGE, 2012)
Nickel Sulphide ore systems in Western Australia are generally small, but very high value. They are typically found in complex geological settings at depth that is beyond the reach of potential geophysical methods. Only seismic methods can be expected to help prospecting such systems. Indeed petrophysical properties of the nickel ore environment in Kambalda region indicated that the ore is likely to cause detectable events. Consequently several experimental 2D and 3D surveys were undertaken by Centre for High Definition Geophysics. In all cases, especially exploring in the volume of rock below about 500m depth high quality seismic images were produced. 2D seismic was mainly used to test seismic response over complex deposits of Yilgarn Craton but also helped refine existing geological models. Subsequent experimental 3D seismic surveys produced high quality images of potential massive sulphide (MS) deposits. In the last two years several of these targets were verified in the Kambalda region. We show several case histories documenting successful application of seismic methods over MS deposits. Despite the success, the high cost of seismic surveys is still an issue for mineral exploration companies.